2015
DOI: 10.1093/rpd/ncv505
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose Measurements for High-Intensity Laser Interactions With Solid Targets at Slac

Abstract: A systematic study of photon and neutron radiation doses generated in high-intensity laser-solid interactions is underway at SLAC National Accelerator Laboratory. These laser-solid experiments are being performed using a 25 TW (up to 1 J in 40 fs) femtosecond pulsed Ti:sapphire laser at the Linac Coherent Light Source's (LCLS) Matter in Extreme Conditions (MEC) facility. Radiation measurements were performed with passive and active detectors deployed at various locations inside and outside the target chamber. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Previous studies show that there were far more photons than other particles outside the target chamber. Some researchers measured the fluence of different kinds of particles and found the fluence of photons was about three orders of magnitude higher than that of neutrons (Liang et al 2016; Yang et al 2017b). By simulating the energy deposited by different particles in the detector, it could be found that at the same energy and the same fluence per area, photons could deposit more energy inside the diamond detector, and each photon can deposit 1 to 5 times as much energy as the neutron deposits.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies show that there were far more photons than other particles outside the target chamber. Some researchers measured the fluence of different kinds of particles and found the fluence of photons was about three orders of magnitude higher than that of neutrons (Liang et al 2016; Yang et al 2017b). By simulating the energy deposited by different particles in the detector, it could be found that at the same energy and the same fluence per area, photons could deposit more energy inside the diamond detector, and each photon can deposit 1 to 5 times as much energy as the neutron deposits.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that almost all the active dosimeters available in the market, including ionization chambers, could not work properly in the radiation field with such an extremely high dose rate. The output values of active detectors were much smaller than that of passive detectors such as thermoluminescence dosimeter (TLD) detectors, which were considered to be accurate (Liang et al 2016). In 2016, Yang and colleagues measured the photon dose generated by an “XG-III” laser device using TLD detectors, optically stimulated luminescence (OSL) detectors, and 451P ionization chambers, and the results indicated that the ionization chambers underestimate the surrounding dose by one to two orders of magnitude compared to the TLD and OSL detectors (Yang et al 2017a; Yang 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Here we try to scale up the radiation doses obtained at TW to sub-PW regime using the dependency between hot electron temperature and the laser intensity. According to the studies on 2014 SLAC-MEC experiments using 25 TW laser [108,109], the hot electron temperature T h was proportional to the square-root of laser intensity. In a 40 TW laser experiment at HI Jena, the hot plasma in Ti bulk was created and the x-ray spectra were studied [110].…”
Section: Appendix B Possible Noise Sourcesmentioning
confidence: 99%
“…In the past years, multiple experiments have been carried out on several laser facilities, like Omega EP [20], LLNL-Titan [34], Vulcan [35,36], Texas [37] SLAC's MEC [38], XGIII [39] and Trident [40] for bremsstrahlung radiation investigation. The characteristics were also investigated by means of particle-in-cell (PIC) simulations [23,24,31,41].…”
Section: Introductionmentioning
confidence: 99%